Analysis of pork price fluctuations during the special era when African swine fever and COVID-19 epidemic coexisted: an empirical study in Macau, China - Xu, Fang; Ni, Xiaoyong; Liu, Kai; Wang, Ming; Tan, Kangye; Hu, Jun (Frontiers in Sustainable Food Systems, 2024)
Emergent crises can exert a catastrophic influence on regional economic systems. Taking the case of Macau’s pig industry, it has been severely impacted by the concurrent outbreaks of African Swine Fever (ASF) and the COVID-19 pandemic over the past few years. This paper analyzes the pork price fluctuations in Macau using the Ensemble Empirical Mode Decomposition (EEMD) method and the Bai-Perron Multiple Structure Breakpoint Test, aiming to characterize the modes of potential crises’ impact on pork prices during that period. It is found that the pork price is primarily correlated with low-frequency component when the original price series is decomposed into high-frequency, low-frequency and trend components, suggesting that long-cycle emergency events should be prioritized when assessing their impact on the pork price. Furthermore, four significant breakpoints in the pork price series curve, corresponding to four major emergent crises, are disinterred through the Bai-Perron multiple structure breakpoint test, enhancing understanding of the underlying reasons of pork price fluctuations in Macau, China, at that time. This study provides a novel perspective to comprehending the impact of crises on regional economic systems.